2022
DOI: 10.1002/lt.26433
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of crossmatch positive simultaneous liver–kidney transplantations in the United States

Abstract: The long‐term outcomes of positive crossmatch (+XM) simultaneous liver–kidney (SLK) transplantations are conflicting. We examined the association between crossmatch status and SLK outcomes in recipients discharged on tacrolimus and mycophenolate with or without steroids. We analyzed the Scientific Registry of Transplant Recipients for all primary SLK recipients between 2003 and 2020 with available crossmatch and induction data. We grouped recipients according to the crossmatch status: negative crossmatch (−XM;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…11 Although overall survival at 1 and 5 y was lower in the HIR patients, further multivariate analyses demonstrated that the only factor that significantly affected survival was a previous kidney transplant, not immunologic status. 11 A recent study by Riad et al 17 showed that patients with a positive crossmatch have a higher risk of early kidney rejection but otherwise comparable outcomes to crossmatch negative recipients. Another study described increased risk of both liver and kidney graft failure and overall patient mortality in SLKT patients with preformed class II DSA; however, confounding factors such as time on dialysis and previous transplant were not considered‚ and immunosuppression protocols were not standardized or current.…”
Section: Discussionmentioning
confidence: 99%
“…11 Although overall survival at 1 and 5 y was lower in the HIR patients, further multivariate analyses demonstrated that the only factor that significantly affected survival was a previous kidney transplant, not immunologic status. 11 A recent study by Riad et al 17 showed that patients with a positive crossmatch have a higher risk of early kidney rejection but otherwise comparable outcomes to crossmatch negative recipients. Another study described increased risk of both liver and kidney graft failure and overall patient mortality in SLKT patients with preformed class II DSA; however, confounding factors such as time on dialysis and previous transplant were not considered‚ and immunosuppression protocols were not standardized or current.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1,2] Despite this, there is currently no consensus regarding the potential impact of prior sensitization or crossmatch testing in simultaneous liver and kidney transplantation (SLKT). Given the conflicting evidence across institutional studies regarding crossmatch results and donor-specific antibodies (DSAs) in SLKT, Riad et al [3] used the Scientific Registry of Transplant Recipients (SRTR) to broadly relate crossmatch results to patient outcomes (patient survival, death-censored kidney and liver graft survival) after SLKT and observed no major effect. We applaud the effort to study this complex population and important topic.…”
Section: Alloantibody and Crossmatch In Simultaneous Liver And Kidney...mentioning
confidence: 99%